Aiding Balkans - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2006)
Conceptual and theoretical issues of foreign aid in post-conflict, transition region are discussed. Two examples are presented in an informal manner. The first is about the incoherence of aid for reconstruction and policies of transition. The second is about the role of expected institutional change that the process of European Union integration provides and the comparative role of aid for institution building. Hypothesis are developed that will be considered in the further work on aid in the Balkans.
Keywords: 330